2009
DOI: 10.14221/ajte.2009v34n1.2
|View full text |Cite
|
Sign up to set email alerts
|

In-Service Teacher Raining in Japan and Turkey: a Comparative Analysis of Institutions and Practices

Abstract: The purpose of this study is to compare policies and practices relating to teacher in-service training in Japan and Turkey. On the basis of the findings of the study, suggestions are made about in-service training activities in Turkey. The research was carried using qualitative research methods. In-service training activities in the two education systems were investigated through visits to the educational institutions and semi-structured interviews. The study indicates that the most important problems facing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 23 publications
4
34
0
5
Order By: Relevance
“…This finding is supportive to the remark that professional development activities in Turkey are carried out by "the organizing authority generally invites an academician from a university or an experienced teacher and asks them to speak for the training activity" (Bayrakcı, 2009). However, the teachers do know what their needs are in relation to their own development.…”
Section: A Person Who Stayed At the University After Graduation Withosupporting
confidence: 68%
“…This finding is supportive to the remark that professional development activities in Turkey are carried out by "the organizing authority generally invites an academician from a university or an experienced teacher and asks them to speak for the training activity" (Bayrakcı, 2009). However, the teachers do know what their needs are in relation to their own development.…”
Section: A Person Who Stayed At the University After Graduation Withosupporting
confidence: 68%
“…Another weakness was that the materials and resources were insufficient and no new materials were developed in the course. These results partially confirmed Bayrakçı (2009) In terms of evaluation of the course, the study found that no feedback and evaluation mechanisms existed. Neither the trainers collected feedback from the trainees nor the Ministry of Education asked for feedback from the trainers or trainees, concurring with Özer (2004) and Bayrakçı (2009) According to the questionnaire results (questions (Q) 1-17), the teachers had positive opinions towards the course in general, especially because the course was motivating and because they were allowed to participate (Q4 & Q5).…”
Section: Program Evaluation Against the Indicators Of Effective Insetmentioning
confidence: 52%
“…Moreover, INSETs in general in Turkey have been reported to suffer from a lot of problems, such as insufficient number of these courses (Küçüksüleymanoğ lu, 2006); top lu, 2006); top-down structure of the courses imposing topics and content selected by others (Bayrakçı, 2009;Odabaș ı ı-Çimer, et al, 2010;Özer, 2004); presentation of the programs in forms of short "one-shot" courses (Daloğ lu, 2004); implementation of lu, 2004); implementation of transmission methods without allowing teachers to reflect on their experiences, participate in learning, and collaborate with peers (Bayrakçı, 2009;Özer, 2004); and lack of follow-up support and evaluation mechanisms (Bayrakçı, 2009).…”
Section: Insets In Turkey and In The Language Education Fieldmentioning
confidence: 99%
“…As Özer (2004) expressed professional development requirements are their interests and attitudes. At this point, the subjects in professional development activities should be aimed at real requirements (needs analysis) of teachers and practices should be monitored (Aydoğan 2002, Bayrakçı 2009, Çiftçi 2008, Demirkol 2010, Özer 2004and Özoğlu 2010.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%